Effects of Pressure Gloves Combined with Hand Training for Post-stroke Hand Edema - Hua LIN; Jing YUAN; Zhilan LIU; Nian WANG; Wen HE; Jing BU; Qianqian MA; Hongbing WANG (康复学报)
Objective:To explore the effects of pressure gloves combined with hand training on post-stroke hemiplegic hand edema in rehabilitation treatment. Methods:A total of sixty post-stroke patients were randomly divided into control group and observation group, with thirty cases in each group. All patients received conventional hand training, such as passive or active joint motion training. In addition to conventional hand training, the patients in the control group wore traditional medical pressure gloves, the patients in the observation group wore customized pressure gloves based on a three-dimensional scanning. Hand edema volume, range of joint motion, Fugl-Meyer assessment(FMA)scale of upper extremity and hand were measured before treatment and after four weeks of treatment. Pressure comfort was assessed with semantic differential method.Results:There were no differences of hand edema volume, range of joint motion and FMA scale of upper extremity between the two groups before treatment(P>0.05).After four weeks of treatment, the hand edema volume in both groups were significantly lower than the volume before treatment(P<0.05).The range of joint motion and FMA scale of upper extremity in both groups were significantly higher than those before treatment(P<0.05).The hand edema volume after treament was significantly lower in the observation group than in the control group(P<0.05).The range of joint motion and FMA scale of upper extremity after treatment were significantly higher in the observation group than in the control group(P<0.05).The score of comfortable sensation was significantly higher in the observation group than in the control group(P<0.05).Conclusion:Pressure gloves combined with hand training can reduce post-stroke hemiplegic hand edema. Customized pressure gloves based on three-dimensional scanning concerned limb curvature have more effectively help to improve rehabilitation result.